2001
DOI: 10.1063/1.1360245
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption state of dimethyl disulfide on Au(111): Evidence for adsorption as thiolate at the bridge site

Abstract: We studied the adsorption state of dimethyl disulfide and methylthiolate on the Au(111) surface by means of the density functional theory (DFT) within a generalized gradient approximation and experimental high-resolution electron energy loss spectroscopy (HREELS) techniques. It turns out that the methylthiolate adsorption is more stable than the dimethyl disulfide adsorption and that the most stable adsorption site for the methylthiolate is the bridge site slightly off-centered towards the fcc-hollow site with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

67
301
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(370 citation statements)
references
References 45 publications
67
301
2
Order By: Relevance
“…In particular, for Au(111) our minimum energy adsorption geometry is identical to that presented by Hayashi et al 48 and by Maksymovych et al 47 The on top site was found to be the most unfavourable one, followed by the hollow site. In all stepped surfaces, the methyl part is oriented above steps and in all cases in such a way that one of the hydrogen atoms is directed towards the surface, whereas the other two are pointing away from the surface.…”
Section: Au(221) Au(331) and Au(332)supporting
confidence: 63%
See 1 more Smart Citation
“…In particular, for Au(111) our minimum energy adsorption geometry is identical to that presented by Hayashi et al 48 and by Maksymovych et al 47 The on top site was found to be the most unfavourable one, followed by the hollow site. In all stepped surfaces, the methyl part is oriented above steps and in all cases in such a way that one of the hydrogen atoms is directed towards the surface, whereas the other two are pointing away from the surface.…”
Section: Au(221) Au(331) and Au(332)supporting
confidence: 63%
“…These results agree with the calculations of Molina and Hammer 8 who found −1.13 eV for (b) and +0.40 eV for (d). For (a), Hayashi et al, 48 report a bridge site adsorption with −0.27 eV per CH 3 S using the PBE exchange-correlation functional. Although the adsorption energy is different, there is good agreement for adsorption geometry.…”
Section: Dissociative Adsorption Of Ch 3 S-sch 3 On Gold Surfacesmentioning
confidence: 99%
“…Calculations were carried out by using the first-principles molecular dynamics program ''STATE'' (Simulation Tool for Atom TEchnology) which has been applied to organic/ metal interfaces [23][24][25][26]. We employed the local density approximation (LDA) [27,28] and the generalized gradient approximation (GGA) [29] for the exchange-correlation energy functional.…”
Section: Methodsmentioning
confidence: 99%
“…We used the Kohn-Sham method in the generalized gradient approximation for the electronic structure calculation, with numerical atomic orbitals (double zeta plus polarization) The initial and relaxed site, the adsorption energy with respect to the fcc-bridge case, the height of the sulfur atom from the gold surface, the average of the three nearest neighbor Au-S distances, and the S-C bond length and angle θ to the surface normal. (81 k-points are used, yielding a converged adsorption energy [20].) as the basis set, by means of the SIESTA program [18].…”
mentioning
confidence: 99%